2013
DOI: 10.1177/1534484313495853
|View full text |Cite
|
Sign up to set email alerts
|

“How” Narratology Narrows the Organizational Theory–Practice Gap

Abstract: In this conceptual piece, we take a narrative approach to explicating the gap between organizational theory and practice. The narrative pentad (what, why, how, who, and when/where) represents six narrative questions metaphorically mapped to the five fingers of the hand. The narrative pentad has successfully served both narrative scholars and practitioners, and we believe that the narrative pentad holds similar promise as a theoretical framework for HRD scholars and practitioners. At the finger tips, spaces bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…By adopting the macromarketing perspective, we identify how Springsteen’s use of narratology leads to his existential authenticity, which helps explain his longevity and economic success. It is through a narratological framework, that our data will show how Springsteen maintains a latent story structure where discursive elements map to story elements (Glibkowski et al , 2014). Although narratology and story have a variety of meanings, and they are often used interchangeably (Shankar et al , 2001), we show the relationships of the concepts in a different but relational light.…”
mentioning
confidence: 87%
“…By adopting the macromarketing perspective, we identify how Springsteen’s use of narratology leads to his existential authenticity, which helps explain his longevity and economic success. It is through a narratological framework, that our data will show how Springsteen maintains a latent story structure where discursive elements map to story elements (Glibkowski et al , 2014). Although narratology and story have a variety of meanings, and they are often used interchangeably (Shankar et al , 2001), we show the relationships of the concepts in a different but relational light.…”
mentioning
confidence: 87%
“…More practically, supervisors can more appropriately gauge when (and why) to use certain resources to motivate employee action. Additionally, addressing the "how-question" (Glibkowski et al, 2014), the three resources (social, task, and money) provide operational standards of actions to be performed. Finally, it has been suggested that the value employees place on different types of resources may be shifting.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
“…Beyond the theoretical contributions of import to scholars, this scale development is also important to practitioners. First, theory is important to practitioners addressing the "what-question" (associated with defining concepts) and the "why-question" (associated with the causal ordering of concepts; Glibkowski, McGinnis, Gillespie, & Schommer, 2014). For example, from a practical perspective, understanding explicitly which resources cause desired outcomes, such as performance, extra-role behavior, and commitment, is useful.…”
mentioning
confidence: 99%
See 2 more Smart Citations